At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve the given equation step-by-step:
[tex]\[\sqrt{3 - 3x} = 3 + \sqrt{3x + 2}\][/tex]
### Step 1: Isolate one of the square root terms
To start, we'll isolate one of the square root expressions. Let's isolate [tex]\(\sqrt{3 - 3x}\)[/tex].
[tex]\[\sqrt{3 - 3x} - \sqrt{3x + 2} = 3\][/tex]
### Step 2: Square both sides to eliminate the square roots
Next, we square both sides of the equation to remove the square roots:
[tex]\[(\sqrt{3 - 3x} - \sqrt{3x + 2})^2 = 3^2\][/tex]
Expanding the left-hand side using the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[(3 - 3x) - 2 \sqrt{(3 - 3x)(3x + 2)} + (3x + 2) = 9\][/tex]
Simplify:
[tex]\[(3 - 3x) + (3x + 2) - 2 \sqrt{(3 - 3x)(3x + 2)} = 9\][/tex]
[tex]\[5 - 2 \sqrt{(3 - 3x)(3x + 2)} = 9\][/tex]
### Step 3: Isolate the square root term again
We now isolate the square root term:
[tex]\[-2 \sqrt{(3 - 3x)(3x + 2)} = 9 - 5\][/tex]
[tex]\[-2 \sqrt{(3 - 3x)(3x + 2)} = 4\][/tex]
Divide both sides by -2 to get:
[tex]\[\sqrt{(3 - 3x)(3x + 2)} = -2\][/tex]
### Step 4: Square both sides again
Now, square both sides to eliminate the square root:
[tex]\[(3 - 3x)(3x + 2) = (-2)^2\][/tex]
[tex]\[ (3 - 3x)(3x + 2) = 4\][/tex]
### Step 5: Expand and simplify
Expand the left side:
[tex]\[ (3 - 3x)(3x + 2) = 9x + 6 - 9x^2 - 6x\][/tex]
[tex]\[ = 9 - 9x^2\][/tex]
So, we have:
[tex]\[9 - 9x^2 = 4\][/tex]
Subtract 4 from both sides to formulate a standard quadratic equation:
[tex]\[9 - 9x^2 - 4 = 0\][/tex]
[tex]\[9 - 9x^2 = 4\][/tex]
### Step 6: Solve the quadratic equation
[tex]\[-9x^2 + 5 = 0\][/tex]
Divide by -1:
[tex]\[9x^2 = 5\][/tex]
Divide by 9:
[tex]\[x^2 = \frac{5}{9}\][/tex]
Take the square root of both sides:
[tex]\[x = \pm \sqrt{\frac{5}{9}}\][/tex]
[tex]\[x = \pm \frac{\sqrt{5}}{3}\][/tex]
### Step 7: Verify potential solutions
We have two potential solutions: [tex]\(x = \frac{\sqrt{5}}{3}\)[/tex] and [tex]\(x = -\frac{\sqrt{5}}{3}\)[/tex]. However, we must check these solutions in the original equation to see if they create true statements or extraneous solutions.
Plugging [tex]\(x = \frac{\sqrt{5}}{3}\)[/tex] into the original equation will reveal whether it holds true.
### Step 8: Conclusion
Upon examination, neither of the potential solutions holds true. Therefore, the original equation has no valid solutions.
The equation:
[tex]\[\sqrt{3 - 3x} = 3 + \sqrt{3x + 2}\][/tex]
has no solution.
[tex]\[\sqrt{3 - 3x} = 3 + \sqrt{3x + 2}\][/tex]
### Step 1: Isolate one of the square root terms
To start, we'll isolate one of the square root expressions. Let's isolate [tex]\(\sqrt{3 - 3x}\)[/tex].
[tex]\[\sqrt{3 - 3x} - \sqrt{3x + 2} = 3\][/tex]
### Step 2: Square both sides to eliminate the square roots
Next, we square both sides of the equation to remove the square roots:
[tex]\[(\sqrt{3 - 3x} - \sqrt{3x + 2})^2 = 3^2\][/tex]
Expanding the left-hand side using the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[(3 - 3x) - 2 \sqrt{(3 - 3x)(3x + 2)} + (3x + 2) = 9\][/tex]
Simplify:
[tex]\[(3 - 3x) + (3x + 2) - 2 \sqrt{(3 - 3x)(3x + 2)} = 9\][/tex]
[tex]\[5 - 2 \sqrt{(3 - 3x)(3x + 2)} = 9\][/tex]
### Step 3: Isolate the square root term again
We now isolate the square root term:
[tex]\[-2 \sqrt{(3 - 3x)(3x + 2)} = 9 - 5\][/tex]
[tex]\[-2 \sqrt{(3 - 3x)(3x + 2)} = 4\][/tex]
Divide both sides by -2 to get:
[tex]\[\sqrt{(3 - 3x)(3x + 2)} = -2\][/tex]
### Step 4: Square both sides again
Now, square both sides to eliminate the square root:
[tex]\[(3 - 3x)(3x + 2) = (-2)^2\][/tex]
[tex]\[ (3 - 3x)(3x + 2) = 4\][/tex]
### Step 5: Expand and simplify
Expand the left side:
[tex]\[ (3 - 3x)(3x + 2) = 9x + 6 - 9x^2 - 6x\][/tex]
[tex]\[ = 9 - 9x^2\][/tex]
So, we have:
[tex]\[9 - 9x^2 = 4\][/tex]
Subtract 4 from both sides to formulate a standard quadratic equation:
[tex]\[9 - 9x^2 - 4 = 0\][/tex]
[tex]\[9 - 9x^2 = 4\][/tex]
### Step 6: Solve the quadratic equation
[tex]\[-9x^2 + 5 = 0\][/tex]
Divide by -1:
[tex]\[9x^2 = 5\][/tex]
Divide by 9:
[tex]\[x^2 = \frac{5}{9}\][/tex]
Take the square root of both sides:
[tex]\[x = \pm \sqrt{\frac{5}{9}}\][/tex]
[tex]\[x = \pm \frac{\sqrt{5}}{3}\][/tex]
### Step 7: Verify potential solutions
We have two potential solutions: [tex]\(x = \frac{\sqrt{5}}{3}\)[/tex] and [tex]\(x = -\frac{\sqrt{5}}{3}\)[/tex]. However, we must check these solutions in the original equation to see if they create true statements or extraneous solutions.
Plugging [tex]\(x = \frac{\sqrt{5}}{3}\)[/tex] into the original equation will reveal whether it holds true.
### Step 8: Conclusion
Upon examination, neither of the potential solutions holds true. Therefore, the original equation has no valid solutions.
The equation:
[tex]\[\sqrt{3 - 3x} = 3 + \sqrt{3x + 2}\][/tex]
has no solution.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.